2019
DOI: 10.1063/1.5110615
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of surface charge dissipation of silicone rubber enhanced by dielectric barrier discharge plasma treatments

Abstract: This paper investigates mechanisms of the surface charge dissipation of silicone rubber (SiR) after dielectric barrier discharge (DBD) plasma treatments in an open air. Electrical and physicochemical properties of the untreated and plasma treated samples were evaluated by surface and volume conductivity, surface potential decay (SPD) measurements, Fourier transform infrared (FT-IR), and water contact angle tests. Results show that the surface conductivity of the plasma treated samples evidently increases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…[57] Electrons are trapped on silicone rubber with binding energies <1 eV. [58] The energy released upon the recombination of PMDS + with a free electron is not known, 8 which probably will be not very different from the ionization energy of the trimethylsilyl radical, 6.5 eV. [60] The kinetic energy of the ions accelerated in the transient cathode fall, by comparison, is less; an estimation with an equation in the monography by Raizer [61] results in <1 eV.…”
Section: Film Formation By Deposition Of Pmds +mentioning
confidence: 99%
“…[57] Electrons are trapped on silicone rubber with binding energies <1 eV. [58] The energy released upon the recombination of PMDS + with a free electron is not known, 8 which probably will be not very different from the ionization energy of the trimethylsilyl radical, 6.5 eV. [60] The kinetic energy of the ions accelerated in the transient cathode fall, by comparison, is less; an estimation with an equation in the monography by Raizer [61] results in <1 eV.…”
Section: Film Formation By Deposition Of Pmds +mentioning
confidence: 99%
“…In material modifications, atmospheric pressure non-thermal plasma is usually generated by dielectric barrier discharge (DBD) [21,23], radiofrequency plasma generator [64] and plasma jet (APPJ) [22,65] working gas in plasma modification to treat the material surface and found that the C-H bond is substituted by the C-F n bond on the treated surface. In studies by Shao et al [23] and Chen et al [21], the plasma treatment was conducted in open air, and it was found that the plasma introduces an O element into the polymer surface, and the chemical reactions produce carbonyl groups. It was found that the plasma treatment method with CF 4 and air as the working gas chemically modified the material surfaces in a manner similar to fluorination and ozonation; thereby, flashover strength can also be effectively improved.…”
Section: Chemical Modification Methodsmentioning
confidence: 99%
“…open air) working gas can be used to treat material surfaces in a manner similar to that of direct fluorination and ozone treatment. In material modifications, atmospheric pressure non‐thermal plasma is usually generated by dielectric barrier discharge (DBD) [21, 23], radiofrequency plasma generator [64] and plasma jet (APPJ) [22, 65], as shown in Figure 4a,b. Lopez‐Garcia et al.…”
Section: Interface Tailoring Methodsmentioning
confidence: 99%
See 2 more Smart Citations